1984
DOI: 10.1002/j.1460-2075.1984.tb02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea mosaic virus VPg: sequencing of radiochemically modified protein allows mapping of the gene on B RNA

Abstract: A partial amino acid sequence of cowpea mosaic virus (CPMV) VPg radiochemically modified by chloramine‐T and Bolton‐Hunter reagent has been determined. VPg covalently bound to viral RNA chains (VPg‐RNA) was iodinated with chloramine‐T and Bolton‐Hunter reagent to label tyrosine and lysine residues, respectively. [125I]VPg‐RNA was digested with nuclease P1 and the resulting [125I]VPg‐pU was purified by SDS‐polyacrylamide gel electrophoresis and subjected to automated Edman degradation. Control experiments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…In polio, CPMV and GFLV, the amino acid sequence for the small 5' genome linked protein (VPg) is located between the NTP-binding and protease proteins (Racaniello & Baltimore, 1988;Goldbach & Rezelman, 1983;Zabel et al, 1984;Pinck et al, 1991). Due to the small size of the VPg and its low degree of conservation the sequence of the VPg cannot be stated with certainty and is only tentatively located as described below and in Fig.…”
mentioning
confidence: 99%
“…In polio, CPMV and GFLV, the amino acid sequence for the small 5' genome linked protein (VPg) is located between the NTP-binding and protease proteins (Racaniello & Baltimore, 1988;Goldbach & Rezelman, 1983;Zabel et al, 1984;Pinck et al, 1991). Due to the small size of the VPg and its low degree of conservation the sequence of the VPg cannot be stated with certainty and is only tentatively located as described below and in Fig.…”
mentioning
confidence: 99%
“…'Pinto'. The B component has been shown to code for the virus-coded polypeptide of the RNA replication complex, VPg, two virus-specific proteases and a polypeptide of 58 000 molecular weight, of unknown function (Franssen et al, 1984;Zabel et al, 1984). It is possible that isolate 7A-4 has a defect in the 58000 mol.…”
Section: -6382 © 1985 Sgmmentioning
confidence: 99%
“…In infected cells the genome RNAs are translated into polyproteins which are subsequently cleaved into functional polypeptides by at least two virus-coded proteases (Goldbach et al, 1981 ;Rezelman et al, 1980;Rottier et al, 1980). The smaller M RNA has been shown to code for the coat proteins: the larger B RNA codes for the proteases, the RNA polymerase and a protein covalently bound to the 5' end of the virion RNA, termed VPg (Daubert et al, 1978;Franssen et al, 1982Franssen et al, , 1984Goldbach et al, 1980Goldbach et al, , 1981Gopo & Frist, 1977;Pelham, 1979;Stanley et al, 1980;Zabel et al, 1984). In comparison with our knowledge of the structure of CPMV and of the synthesis and processing of virus proteins, little is known about such 'biological' aspects of CPMV as the determinants of host range.…”
mentioning
confidence: 99%
“…VPg has been shown to be encoded by B-RNA (Stanley et al, 1980;Zabel et al, 1982), and mapping of its sequence on the open reading frame of B-RNA has revealed that it comprises 28 amino acid residues (Zabel et al, 1984;Wellink et al, 1986). Its immediate precursor is probably a membrane-bound Mr 60 000 (60K) protein .…”
Section: Introductionmentioning
confidence: 99%